Analysis of the Сonstruction Market in Russia and Abroad in Order to Сurb the Growth of Construction Costs and Ensure the Сompetitiveness of Enterprises by Increasing the Efficiency of the Cost Accounting and Сontrol System - A. E. Lebedeva; I. V. Karakozova (Управленческие науки, 2024)
The purpose of the study is to analyze the Russian construction market and the prospects for its development in the context of large contracting companies, as well as to determine contractor competitiveness and the place of the largest domestic construction companies in the world ranking. Comparison, analysis, as well as graphical, tabular methods of data presentation and visualization were used as research methods. The paper presents an analysis and characteristics of the Russian and world construction market, its dynamics, structure and key players. The main trends and drivers of the construction industry are described. The volume of construction is growing every year, despite the economic and political crises of past five years. This fact indicates a high demand for construction products. The article considers the main players in the Russian and foreign markets. The leading positions in terms of construction volumes are occupied by such countries as China, the USA, Japan and the EU, while the Russian Federation lags behind in terms of construction production volume. Only four construction companies in the world have a turnover of more than $ 100 billion, while maintaining a significant lead over other players. Whereas the development of the global construction market is associated with population dynamics, an influx of investments in the Asian region is expected, which in turn will contribute to the development of technologies and the introduction of innovations in the field of construction management. The study revealed a direct correlation and relationship between the competitiveness of construction companies and internationalization. Despite the increasing interest of Russian developers in foreign projects, at the moment the expansion trend of Russian construction companies is just beginning to take shape. It is concluded that in order to increase the competitiveness of Russian construction companies in the world market, the efficiency of project management and cost optimization, it is necessary to introduce an effective system of projects cost accounting and control.